Comparative Analysis of Online and Offline Lectures during the Covid-19 Pandemic - Retno Dewi Noviyanti; Dewi Pertiwi Dyah Kusudaryati; Dodik Luthfianto (Urecol Journal. Part A: Education and Training, 2021)
During the Covid-19 pandemic, learning that was originally carried out with an offline system turned into an online system. Online learning is the right solution in maintaining health from transmission of the Covid-19 virus. Both online and offline learning have their own strengths and weaknesses. The purpose of this study was to analyze the comparison of online and offline theoretical lectures for students of the Undergraduate Nutrition Program at ITS PKU Muhammadiyah Surakarta during the Covid 19 pandemic. in the form of accidental sampling. The results showed that there are weaknesses and strengths of learning with online and offline methods. The weaknesses of the online method mostly mention that the quota is wasteful and if the signal is constrained, the learning material becomes less than the maximum, respectively by 37.1%, while the advantages of the online method mostly state that learning can be done anytime and anywhere by 57.3%. The weaknesses of the offline method mostly state that learning starts sometimes not ontime by 24.7%, the advantages of the offline method mostly state that if there is material that is not understood, you can immediately ask and get examples directly by 35.9%. The results in general, students prefer theory lectures to be carried out offline by 70.8%. The conclusion of this study is that the ITS PKU Muhammadiyah Surakarta S1 Nutrition students prefer theoretical lectures to be carried out offline during the Covid-19 pandemic.